2011
DOI: 10.3174/ajnr.a2508
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Application of Postmortem Diffusion-Weighted and Diffusion Tensor MR Imaging of the Human Brain in Situ

Abstract: BACKGROUND AND PURPOSE: DWI and DTI of the brain have proved to be useful in many neurologic disorders and in traumatic brain injury. This prospective study aimed at the evaluation of the influence of the PMI and the cause of death on the ADC and FA for the application of DWI and DTI in forensic radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 38 publications
7
36
0
Order By: Relevance
“…26,27 In addition, Kobayashi et al 27 noted a significant decrease of the apparent diffusion coefficient (ADC) value. Scheurer et al 53 confirmed this finding and observed a correlation between decreasing ADC values and increasing post-mortem intervals. They also found that the ADC values were generally lower in cases with traumatic and hypoxic brain injuries than in cases of heart failure.…”
Section: Step 3: Post-mortem Mr From Head To Toe Head and Neck Imagingsupporting
confidence: 73%
See 1 more Smart Citation
“…26,27 In addition, Kobayashi et al 27 noted a significant decrease of the apparent diffusion coefficient (ADC) value. Scheurer et al 53 confirmed this finding and observed a correlation between decreasing ADC values and increasing post-mortem intervals. They also found that the ADC values were generally lower in cases with traumatic and hypoxic brain injuries than in cases of heart failure.…”
Section: Step 3: Post-mortem Mr From Head To Toe Head and Neck Imagingsupporting
confidence: 73%
“…They also found that the ADC values were generally lower in cases with traumatic and hypoxic brain injuries than in cases of heart failure. 53 Further research is currently underway to investigate and characterize how normal post-mortem changes, such as decomposition and changes in body temperature, affect the quality of PMMR and various MR parameters, including ADC values. Both Añon et al 49 and Yen et al 48 compared PMMR (and PMCT) of the head to autopsy.…”
Section: Step 3: Post-mortem Mr From Head To Toe Head and Neck Imagingmentioning
confidence: 99%
“…8,9 Because radiological imaging became routine in forensic investigation with the application of postmortem computed tomography (PMCT), PMCT angiography, and postmortem magnetic resonance (PMMR), additional technologies such as molecular magnetic resonance and diffusion-weighted imaging are being explored for their diagnostic benefit. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] The purpose of this study was to evaluate the feasibility of postmortem DTI (PMDTI) in forensics, as well as its influencing factors and correlation to the cause of death compared with autopsy.…”
mentioning
confidence: 99%
“…There is evidence that these techniques can be used in the post-mortem setting, although the normal post-mortem appearance is radically different to the clinical normal, but may help with both time from death and cause, particularly in relation to the brain. 29,[97][98][99] CONCLUSIONS What is clear from the multitude of research avenues is that the scientific community is still a long way from understanding the detailed post-mortem physiological changes that dictate tissue changes, contrast dispersal patterns and complex imaging findings. However, much has been learnt, and there is no doubt that imaging should be used in many different indications in the investigation of death.…”
Section: Other Approachesmentioning
confidence: 99%